Comparative Analysis of Structural Response to Blast Loading in Plain and Reinforced Concrete Walls - Muazu, N.; Mustapha, B. G.; Mohammed, K.; David, I. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2026)
This study presents a comparative numerical evaluation of the structural response of plain and reinforced concrete (RC) walls subjected to blast loading, with emphasis on the influence of wall geometry and reinforcement on blast resistance. Finite element simulations were conducted in ANSYS AUTODYN using a 100 kg TNT charge at a stand-off distance of 1 m. Three wall configurations, flat, L shaped, and U-shaped, were analyzed with and without reinforcement, and their performance was assessed in terms of equivalent stress, strain, total deformation, and damage evolution. The results show that flat plain concrete walls experienced the most severe response, with peak stresses exceeding 9 MPa, strains above 13 mm/mm, large deformations of approximately 385 mm, and rapid damage progression leading to early failure. Reinforcement improved performance in all geometries; however, geometric configuration played a more dominant role in blast mitigation. Among all configurations, the U-shaped reinforced concrete wall exhibited superior performance, recording minimal peak stress (~0.3 MPa), the lowest strain response (~3 mm/mm), negligible deformation (< 0.05) in damage reduction across wall types, leading to the rejection of the null hypothesis. The findings demonstrate that the combination of reinforcement and optimized U-shaped geometry provides the most effective blast resistance, offering critical guidance for the design of blast-resilient concrete wall systems in high-risk environments.